Transposition technique of translating personification in Kahlil Gibran’s novel, The Broken Wings - Tatu Siti Rohbiah; Uup Gufron (Jurnal Bebasan, 2025)
This research is intended to describe and analyze the transposition technique in translating personification in Kahlil Gibran's novel The Broken Wings, and the factors that cause non-equivalence between the source language (SL) and the Indonesian translation, Sayap-Sayap Patah (TL). This research focuses on identifying grammatical transposition techniques. The researcher uses a qualitative method with content analysis. The study identified 89 examples of personification translation, indicating that transposition techniques play an essential role in achieving equivalence. Examples of this case in class shifts, such as the verb "greet" translated into Indonesian as the noun salam, as well as intersystem shifts such as "the earth" to bumi without a definiteness marker, indicate the necessary structural adaptation between English and Indonesian. These shifts reflect the structural asymmetry that affects translation, although this technique is effective in many cases, non-equivalence remains. In conclusion, this research underscores the importance of a thorough understanding of transposition techniques in literary translation and offers practical insights to help academics and translators improve translation quality.